Beyond vessels: unraveling the impact of VEGFs on neuronal functions and structure : review - Aksan, Bahar; Mauceri, Daniela (Journal of biomedical science, 2025)
Neurons rely on the bloodstream for essential nutrients and oxygen, which is facilitated by an intricate coupling of the neuronal and vascular systems. Central to this neurovascular interaction is the vascular endothelial growth factor (VEGF) family, a group of secreted growth factors traditionally known for their roles in promoting endothelial cell proliferation, migration, and survival in the cardiovascular and lymphatic systems. However, emerging evidence shows that VEGFs also play indispensable roles in the nervous system, extending beyond their canonical angiogenic and lymphangiogenic functions. Over the past two decades, VEGFs have been found to exert direct effects on neurons, influencing key aspects of neuronal function independently of their actions on vascular cells. In particular, it has become increasingly evident that VEGFs also play crucial functions in the development, regulation, and maintenance of neuronal morphology. Understanding the roles of VEGFs in neuronal development is of high scientific and clinical interest because of the significance of precise neuronal morphology for neural connectivity and network function, as well as the association of morphological abnormalities with neurological and neurodegenerative disorders. This review begins with an overview of the VEGF family members, their structural characteristics, receptors, and established roles in vasculature. However, it then highlights and focuses on the exciting variety of neuronal functions of VEGFs, especially their crucial role in the development, regulation, and maintenance of neuronal morphology.
Gesehen am 13.08.2025